Post-harvest Quality Evolution of Jonagored Apples (Mallus domestica cv. Borkh) during Shelf life Storage - Fahrizal Yusuf Affandi; Bert Verlinden (APTA and DTIP FTP UGM, 2017)
The experiment was carried out to study the quality evolution of Jonagored apples (Mallus domestica cv. Borkh) during 14 days of shelf life prior to controlled atmosphere (CA) storage. The apple were harvested from the “Fruitteelt centrum” (Velm, Belgium) in 24 September 2010 (optimal picking) and 8 October 2010 (late picking) and were stored at 18°C and 65% RH to mimic the shelf life condition. The apple then were measured for colour, firmness, soluble solid content (SSC), titratable acidity, ethylene production rate, O 2 consumption rate, CO 2 production rate and respiratory quotient (RQ) at 0, 7 and 14 days after harvest. There was a significant effect of shelf life duration in colour of the apple. The apple turn its colour from green to yellowish green at the end of shelf life. The optimal-harvested apple had a greener colour than the late-harvested apple at 0 and 7 days of shelf life except at 14 days where the older apple had a greener colour. Although the effect was not consistent, firmness of apple was affected by shelf life and picking time as well. Firmness decreased along shelf life and the optimal-harvested apples were firmer than the late-harvested apple. Apple’s acidity decreased during shelf life from 8,43 mL NaOH (optimal-harvested apple) and 8.85 mL NaOH (late- harvested apple) to 7.58 mL NaOH (optimal-harvested apple) and 7.03 mL NaOH (late- harvested apple) at the end of shelf life. Yet, acidity was not affected by picking time. Ethylene was considerably increased throughout shelf life and the late-harvested apple had a higher ethylene production level than the optimal-harvested apple. Optimal-harvested apple had a lower respiration rate than the late picked apple. Older apple consumed oxygen and produced carbon dioxide at a higher rate than the younger apple. Moreover, respiration rates as represented by O 2 consumption rate, CO 2 production rate and respiratory quotient (RQ) tended to increase along shelf life.